ChemInform Abstract: Sulfur—Carbon Bond Formation Through Ring‐Opening of Triazolothiadiazole with Organometallics. Issue 6 (February 2015) - Othman, Raja Ben; Massip, Stephane; Marchivie, Mathieu; Jarry, Christian; Vercouillie, Johnny; Chalon, Sylvie; Guillaumet, Gerald; Suzenet, Franck; Routier, Sylvain
Abstract S‐substituted thiotriazoles are formed from triazolothiadiazoles and arylcuprates, Grignard‐reagents and organolithium compounds.